2014
DOI: 10.7196/samj.6578
|View full text |Cite
|
Sign up to set email alerts
|

National expenditure on health research in South Africa: What is the benchmark?

Abstract: The Mexico (2004), Bamako (2008) and Algiers (2008) declarations committed the South African (SA) Ministry of Health to allocate 2% of the national health budget to research, while the National Health Research Policy (2001) proposed that the country budget for health research should be 2% of total public sector health expenditure. The National Health Research Committee has performed an audit to determine whether these goals have been met, judged by: (i) health research expenditure as proportions of gross expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The patient demographic profile was similar to that in previous studies from SA and elsewhere. [10][11][12][13][14] Sixty-five percent were males, and scald injuries predominated. Eighty-five percent of patients were in the lowest socioeconomic category, denoting that they would not be expected to pay for health services.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient demographic profile was similar to that in previous studies from SA and elsewhere. [10][11][12][13][14] Sixty-five percent were males, and scald injuries predominated. Eighty-five percent of patients were in the lowest socioeconomic category, denoting that they would not be expected to pay for health services.…”
Section: Researchmentioning
confidence: 99%
“…The Consensus Report on Revitalising Clinical Research in SA of the Academy of Science of South Africa (ASSAf) identified the low level of investment in clinical research as a major factor in SA's declining clinical research performance. [14] This is the first SA study to focus on healthcare resource utilisation for hospitalised paediatric burn survivors. Such research is essential to evaluate current management policies and identify new healthcare strategies, with the objective of reducing costs while maintaining good clinical practice.…”
Section: Researchmentioning
confidence: 99%
“…They recommend that a new set of realistic, transparent, internationally accepted and clearly defined targets be adopted forthwith as a means of ensuring adequate future government investment in health research in SA, and that an efficient monitoring mechanism be developed to track the level of expenditure on health research by governmental and non-governmental funders in the national health research system, so that performance against new benchmarks can be assessed accurately. [1] …”
Section: National Expenditure On Health Research In Samentioning
confidence: 99%
“…Against the background of the Ministry of Health's commitment to allocate at least 2% of the national health budget to research, the National Health Research Committee has performed an audit [1] to establish the extent to which SA has historically invested in health research, judged by: (i) health research expenditure as proportions of the gross expenditure on research and development and the gross domestic product; and (ii) the proportion of the national health budget and the Department of Health budget apportioned to research.…”
Section: National Expenditure On Health Research In Samentioning
confidence: 99%
“…The call for greater financial investment in health research within the public sector, to 2% of the national health budget, should be factored into the current issue. [6] Due regard and recognition should be given to the unique role of registrars as registered university students who work in full-time jobs (including overtime) as part of their clinical training, and are required to successfully deliver a Master's-level research project. Achieving this within a defined 4-year training period while honouring the dictates of the employer (clinical training body), the university (academic body), the CMSA (assessment/examining body) and the HPCSA (registering body) is a balancing act.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%